GTMalpha - Towards a Graphical Notation for Topic Maps - THOMAS, HENDRIK (LIV Series University of Leipzig, Germany, 2008)
In the last years several drafts, recommendations and concepts for a graphical notation for Topic Maps have been published, but till today no graphical notation is generally approved and used in the Topic Maps community. In this paper we present GTMalpha as a conceptual new notation for a graphical representation of Topic Maps. Our objective is, to provide a practical usable notation, which allows a complete, consistent as well as easy to use graphical representation of any given topic map draft. GTMalpha provides a domain as well as a subject centric view and most important it considers the unique characteristics of the Topic Maps paradigm. This paper serves as a user oriented GTMalpha manual for ontology designers, domain experts as well as users.
PUBLISHED
Keywords: Computer Science